Prevalence of clinical and subclinical caprine mastitis of northern region in Bangladesh (Progressive Agriculture, 2018)
Mastitis is a multifactorial and infectious disease of the udder of dairy animals. Infected animals suffer from pain and fever and causing damage in udder and changes in milk. The aim of this work was to determine the prevalence of clinical and sub-clinical caprine mastitis associated with bacterial pathogens during the period from January to June, 2017. A total of 120 lactating goats were randomly selected from different villages of Dinajpur district and 240 milk samples from each udder half were aseptically collected. The udders were examined and screened for the evidence of clinical and subclinical mastitis by clinical examination of udders and examining milk samples. Subclinical mastitis was detected by California Mastitis Test (CMT). Milk samples of all clinical and subclinical mastitis goats were cultured in/on bacteriological media for isolation and characterization of responsible bacterial pathogens. The overall prevalence of clinical and subclinical mastitis in goats was found to be 11.67% and 38.75%, respectively. Bacteriological examination of mastitic milk samples of caprine revealed Staphylococcus spp. (32.5%) as the major pathogen followed by Escherichia coli (22.5%), Pseudomonas spp. (12.5%), Klebsiella spp. (12.5%) and Bacillus spp. (5%). Results of this study indicated that about 50% of caprine udder were infected with mastitis (38.75%), which may render lowering milk production and mortality of goats and kids. It needs to screen milk sample of lactating goats by CMT, identify mastitic goats with infected bacteria, evaluate antibiotic sensitivity and design control strategy accordingly.Progressive Agriculture 29 (2): 127-138, 2018